Non-Projective Two-Weight Codes - Kurz, Sascha (Entropy, 2024)
It has been known since the 1970’s that the difference of the non-zero weights of a projective (Formula presented.) -linear two-weight code has to be a power of the characteristic of the underlying field. Here, we study non-projective two-weight codes and, e.g., show the same result under mild extra conditions. For small dimensions we give exhaustive enumerations of the feasible parameters in the binary case.
CRIS-Team Scopus Importer:2025-02-04
Keywords: linear codes; two-character sets; two-weight codes